2004
DOI: 10.1016/j.molcel.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of RhoGDI by Pak1 Mediates Dissociation of Rac GTPase

Abstract: Selective activation of Rac GTPase signaling pathways requires the specific release of Rac from RhoGDI complexes. We identified a RhoGDI kinase from bovine brain as p21-activated kinase (Pak). Pak1 binds and phosphorylates RhoGDI both in vitro and in vivo at Ser101 and Ser174. This resulted in dissociation of Rac1-RhoGDI, but not RhoA-RhoGDI, complexes, as determined by in vitro assays of complexation and in vivo by coimmunoprecipitation analysis. We observed that Cdc42-induced Rac1 activation is inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(227 citation statements)
references
References 46 publications
11
208
3
5
Order By: Relevance
“…Additionally, a number of signaling cascades leading to the phosphorylation of either the Rho GTPase or to Rho GDI itself (DerMardirossian and Bokoch, 2005) have been shown to modulate RhoGDI-Rho GTPase complexation directly. Recently, we established that the phosphorylation of RhoGDI on two sites concurrently by p21-activated kinase 1 (Pak1) leads to a selective release of Rac from RhoGDI complexes and that this activity was necessary for Rac activation by growth factors (DerMardirossian et al, 2004).Here we provide evidence that Src serves as a RhoGDI kinase in vitro and in vivo and demonstrate a specific effect of phosphorylation on Rho GTPase-RhoGDI association. Further, we show that this phosphorylation plays a unique role in modulating the persistent localization of RhoGDI to the plasma membrane and that tyrosine phosphorylation of RhoGDI by Src results in enhanced Rho GTPase cytoskeletal activity.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, a number of signaling cascades leading to the phosphorylation of either the Rho GTPase or to Rho GDI itself (DerMardirossian and Bokoch, 2005) have been shown to modulate RhoGDI-Rho GTPase complexation directly. Recently, we established that the phosphorylation of RhoGDI on two sites concurrently by p21-activated kinase 1 (Pak1) leads to a selective release of Rac from RhoGDI complexes and that this activity was necessary for Rac activation by growth factors (DerMardirossian et al, 2004).Here we provide evidence that Src serves as a RhoGDI kinase in vitro and in vivo and demonstrate a specific effect of phosphorylation on Rho GTPase-RhoGDI association. Further, we show that this phosphorylation plays a unique role in modulating the persistent localization of RhoGDI to the plasma membrane and that tyrosine phosphorylation of RhoGDI by Src results in enhanced Rho GTPase cytoskeletal activity.…”
mentioning
confidence: 72%
“…Additionally, a number of signaling cascades leading to the phosphorylation of either the Rho GTPase or to Rho GDI itself (DerMardirossian and Bokoch, 2005) have been shown to modulate RhoGDI-Rho GTPase complexation directly. Recently, we established that the phosphorylation of RhoGDI on two sites concurrently by p21-activated kinase 1 (Pak1) leads to a selective release of Rac from RhoGDI complexes and that this activity was necessary for Rac activation by growth factors (DerMardirossian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…RhoGDI is known to be a downstream effector of PAK1 (27). RhoGDI phosphorylation by PAK1 dissociates Rac1 from RhoGDI, allowing subsequent Rac1 activation by Rac guanine nucleotide exchange factors (27).…”
Section: Arf6 Distinctly Modulates Dendritic Spine Formation At Eachmentioning
confidence: 99%
“…RhoGDI phosphorylation by PAK1 dissociates Rac1 from RhoGDI, allowing subsequent Rac1 activation by Rac guanine nucleotide exchange factors (27). Because previous studies showed that the spine-promoting effect of ARF6 is partially blocked by a dominant negative Rac1 (13), we tested the involvement of the PAK1/RhoGDI pathway using ARF6-T157A.…”
Section: Arf6 Distinctly Modulates Dendritic Spine Formation At Eachmentioning
confidence: 99%
“…The demonstration that positive crosstalk occurs via modulation of GDI activity (69) raises the possibility that GDIs could also mediate negative crosstalk. It is also possible that crosstalk could occur more indirectly, at the level of the cytoskeleton, for instance by controlling the local assembly and disassembly of a cytoskeletal scaffold.…”
Section: Feedback and Crosstalkmentioning
confidence: 99%